Магнітографічні та спектральні дослідження сонячних магнітних полів в Астрономічній обсерваторії Київського національного університету імені Тараса Шевченка у 1975–1980 рр. - Лозицький, Всеволод Григорович (Київський національний університет імені Тараса Шевченка, 2021)
1975 р. в Астрономічній обсерваторії Київського національного університету імені Тараса Шевченка встановлений і почав діяти магнітограф повного вектора конструкції СибІЗМІР, і це ініціювало створення в обсерваторії нового перспективного наукового напряму – вимірювання сонячних магнітних полів як магнітографічним, так і спектрально-поляризаційним методом. У цій статті наведено короткий огляд хронології подій у перші 5 років існування нового напряму, а також найважливіших наукових результатів у цей період. Зокрема, тоді отримано нові дані про існування магнітних полів напруженістю ≈ 10 кГс в активних областях на Сонці, про дискретність напруженостей у субтелескопічних структурах із дуже сильними полями, а також дані про суттєве пригнічення в них турбулентних рухів. Відповідні висновки підтверджено і деталізовано новими подальшими дослідженнями.

In 1975, at the Astronomical Observatory of the Taras Shevchenko National University of Kyiv, a magnetograph of the full vector of the SIBIZMIR design was installed and began to operate, and this initiated the creation of a new promising scientific direction at the observatory - the measurement of solar magnetic fields by both magnetographic and spectral-polarization methods. This article provides a brief chronology of the events in the first 5 years of the existence of the new direction, as well as the most important scientific results during this period. Вased on the experience of observations obtained at the Kyiv observatory, it was concluded that this magnetograph in the Kyiv’s astroclimate can not provide such scientifically valuable data as those magnetographs used in other observatories far outside large cities. In particular, although in Kyiv the sensitivity of measurements in the longitudinal magnetic field channel was quite high – about 5 G in the longitudinal field channel and 75 G in the transverse field channel, "noise" in the radial velocity channel reached 0.3 km/sec, which is about an order of magnitude higher than in the Crimea magnetograph. Another reason for the limited use of the magnetograph in the Kyiv observatory was that in the late 1970s significant problems with the calibration of magnetographic measurements became apparent, as a result of which such measurements in the areas of sunspots could have errors of 200–300%. However, in parallel with magnetographic research, spectral-polarization studies were also developed, and they allowed to obtain the most important results. In particular, the new data were obtained on the existence of magnetic fields with a strength of ≈ 10 kG in active regions on the Sun, on the discreteness of the strengths in subtelescopic structures with very strong fields, as well as data on the significant suppression of turbulent motions in them. The corresponding conclusions were confirmed and detailed by new research in the following years.
Magnetographic and spectral investigations of solar magnetic fields in Astronomical observatory of Taras Shevchenko National University of Kyiv in 1975–1980
Keywords: Сонце; сонячна активність; спектральні дослідження; ефект Зеємана; магнітні поля; сонячний магнітограф; Sun; solar activity; spectral investigations; the Zeeman effect; magnetic fields; solar magnetograph